Pengaruh Penyuluhan Agama Kristen Terhadap Perkembangan Sosio-Emosional Lansia Di Desa Siaro Kecamatan Siborongborong Kabupaten Tapanuli Utara - Grace Debora Romaito Simamora; Luhut Mawardi Sihombing; Regina BM. Nainggolan; Agnes Novianti Permata Sari; Tiur Imeldawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine the positive and significant influence of Christian religious counseling on the socio-emotional development of the elderly in Siaro Village, Siborongborong District, North Tapanuli Regency. This research employed a descriptive quantitative approach and involved 27 respondents as the research subjects. The data were collected using a closed-ended questionnaire consisting of 20 items for each variable. The data were then analyzed using the Kolmogorov–Smirnov normality test, Product Moment correlation test (rxy), t-test, and simple regression analysis. The results of the analysis showed that: (1) Analysis prerequisite tests: a) in the positive relationship test, the value of rxy = 0.570 was greater than rtable = 0.381, indicating a positive relationship between Christian religious counseling (X) and the socio-emotional development of the elderly (Y); b) in the significance test, the value of tcount = 1.982 was greater than ttable = 1.706 at a significance level of α = 0.05, indicating that the relationship was significant. (2) Influence test: a) in the regression equation test, the equation Y = 8.207 + 0.636X was obtained, which indicates that every increase of one unit in Christian religious counseling increases the socio-emotional development of the elderly by 0.636 units; b) the regression coefficient of determination (R²) = 0.570 indicates that 57.0% of the variation in the socio-emotional development of the elderly can be explained by Christian religious counseling, while the remaining 33% is influenced by factors outside this study. Therefore, Ha is accepted and Ho is rejected, indicating that Christian religious counseling has a positive and significant influence on the social and emotional development of the elderly.